Pseudo-Random Identification and Efficient Privacy-Preserving V2X Communication for IoV Networks - Sujash Naskar; Gerhard Hancke; Tingting Zhang; Mikael Gidlund (IEEE Access)
The advancement of Internet of Vehicles (IoV) technologies has significantly enhanced road safety and transportation efficiency through smart traffic management and precise control systems. With the advent of 5G and beyond, vehicles within the IoV ecosystem can seamlessly communicate with various smart entities (X) using V2X (Vehicle-to-Entity) communications. However, the openness of IoV networks and the exponential growth of V2X links have expanded potential attack surfaces, increasing the risk of security and privacy breaches. In response to these challenges, this article proposes a privacy-preserving and secure communication framework for IoV networks, addressing critical security challenges in V2X communication. By leveraging lightweight cryptographic mechanisms such as hash functions, quadratic residuosity, and Legendre symbols, the proposed scheme ensures secure authentication, group key sharing, and pseudonym management within IoV networks. The proposed scheme’s security and privacy features, along with its correctness, have been rigorously validated against various security threats where other state-of-the-art schemes fail. Comprehensive performance analysis demonstrates that our scheme completes authentication in a fraction of a millisecond, significantly outperforming existing approaches. The design simplicity and efficiency of the proposed authentication structure make it highly suitable for real-world IoV applications.